Capturing/interpreting non-obvious slope controlling structures - Mathis, J.I. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Rock slope stability is, in many cases, controlled by throughgoing continuous planes, or fracture zones, within the rock mass. In many cases, these features are not obvious and are ignored during base level data collection. Failure to capture these features, or zonal swarms of parallel geologic structures, results in either conservatism in slope design, where experience dictates slope angles should be reduced, or in slopes that incorporate structural features that are likely to experience/control instability. Often, when such slope failures occur, the practitioner stretches to increasingly diverse failure modes incorporating rock bridges, step path failure, etc. when the failure is, in actuality, controlled by non-obvious, existing continuous structural features that were simply not defined or interpreted improperly. This failure to properly capture/interpret structural features continues even during slope failure delineation programs as the programs implemented are improperly configured, and the technical personnel assigned are unaware of the techniques necessary to properly quantify these features. This paper illustrates some of the methods utilised, together with demonstrated examples of evaluating and interpreting such structural features, or swarms of features, and the impact on rock slope design.